Meeting the needs of the aviation industry through aviation maintenance technician schools. (11th July 2006) - Williams, Michael J.; Rhoades, Dawna L.
There is an acknowledged shortage of trained aviation technicians within the aviation industry, particularly in the USA. While initiatives have been proposed to replace those retiring from the industry or leaving for other industries, a major concern is the ability to provide qualified entry level technicians. This paper investigates the role and capabilities of FAA approved Aviation Maintenance Technician Schools (AMTS) in supplying qualified technicians for an environment of increasingly complicated aircraft, dwindling maintenance budgets and increased flight schedules. A preliminary study was conducted that included over 25% of the 176 AMTSs currently approved by the FAA. The study explored over 50 attributes of each school to examine current practices and capabilities, and recommend ways to meet industry needs in the coming years. Results showed trends in enrolments, expected graduates, and plans for expansion or change. Other data such as tuition, programme capabilities and student demographics are also discussed.